2009
DOI: 10.1089/jop.2008.0072
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ocular Adverse Effects in Patients Treated With Topical Prostaglandin Analogs: Changes in Prescription Patterns and Patient Persistence

Abstract: Ocular adverse effects, particularly hyperemia, negatively affect patient continuation with therapy and switching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 21 publications
3
71
2
5
Order By: Relevance
“…The development of less toxic antiglaucoma treatment may reduce damage to the eye surface (Doughty 2012) and improve patient compliance towards medical therapy (Messmer et al 2012). Such improvements could improve quality of life, which is strongly affected by eye surface adverse effects in patients with glaucoma (Zimmerman et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The development of less toxic antiglaucoma treatment may reduce damage to the eye surface (Doughty 2012) and improve patient compliance towards medical therapy (Messmer et al 2012). Such improvements could improve quality of life, which is strongly affected by eye surface adverse effects in patients with glaucoma (Zimmerman et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…(Odberg et al, 2001) Hahn has identified 3 patient-centered strategies for helping physicians detect and address patient adherence to glaucoma medication, recognizing that patients naturally want their physicians to see them as good patients. (Hahn, 2009) The first strategy is a 4-step adherence assessment interview that redefines the good patient as someone who works collaboratively with their physician to overcome the normal barriers to adherence, rather than as someone who adheres to treatment. By inquiring about what the patient understands about their medication regimen, and explaining how difficult taking medications can be, how common nonadherence is, and that treatment decisions depend on truthfully knowing whether patients have adhered to their medications, the physician creates a bond of trust and acceptance with the patient around the topic of adherence.…”
Section: Methods For Improving Adherencementioning
confidence: 99%
“…In an attempt to determine the cause of nonpersistence, Zimmerman et al examined the association between ocular adverse effects of certain topical glaucoma medications, changes in prescription patterns, and rates of persistence. (Zimmerman et al, 2009) Using a pharmacy claims database, patients' medical charts, and telephone interviews with patients and physicians, they found that persistence rates for continuous refills of the PGAs were 11% for latanoprost, 9% for bimatoprost, and 5% for travoprost. The most common reason for switching medications was lack of efficacy (43%), followed by adverse effects (19%).…”
Section: Persistence Rates For Glaucoma Medicationsmentioning
confidence: 99%
“…However, their effect on the trabecular meshwork remains unclear (Oh et al, 2006;Johnson et al, 2010). There was no statistically significant difference in efficacy between the 3 commercially available topical prostaglandin analogues but there was a reported borderline increased incidence of ocular hyperaemia with bimatoprost (van Not available for patient use www.intechopen.com de Valk et al, 2005;Zimmerman et al, 2009). Bimatoprost has the edge in effectiveness but with slightly more pronounced side effects (Cracknell and Grierson, 2009).…”
Section: Prostaglandin Analoguesmentioning
confidence: 99%